2014
DOI: 10.1111/faf.12084
|View full text |Cite
|
Sign up to set email alerts
|

A collective navigation hypothesis for homeward migration in anadromous salmonids

Abstract: Anadromous salmon (genera Oncorhynchus and Salmo) spend much of their lives feeding in productive northern oceans and then return home to natal sites for reproduction with remarkable accuracy. The mechanisms used for navigation by individuals during migrations are thought to include geomagnetic, celestial and olfactory cues, but rarely are social interactions between individuals considered. Mounting evidence from other taxa indicates that individuals in larger groups can better sense and respond to environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(113 citation statements)
references
References 138 publications
(191 reference statements)
5
108
0
Order By: Relevance
“…This point was made by Schmidt et al , who showed that eavesdropping on the reproductive performance of conspecifics can enhance breeding habitat selection and, consequently, population growth. When individuals gain reproductive benefits by using social information that increases in abundance or quality with the density of information-producing individuals [21,22,[28][29][30], this [24,83]. While usually beneficial, reliance on social information can be detrimental if followed leaders are misinformed; for instance (D) bison (Bison bison) have been led by misinformed individuals to foraging grounds with high mortality risk due to hunting by humans [40].…”
Section: Glossarymentioning
confidence: 99%
See 2 more Smart Citations
“…This point was made by Schmidt et al , who showed that eavesdropping on the reproductive performance of conspecifics can enhance breeding habitat selection and, consequently, population growth. When individuals gain reproductive benefits by using social information that increases in abundance or quality with the density of information-producing individuals [21,22,[28][29][30], this [24,83]. While usually beneficial, reliance on social information can be detrimental if followed leaders are misinformed; for instance (D) bison (Bison bison) have been led by misinformed individuals to foraging grounds with high mortality risk due to hunting by humans [40].…”
Section: Glossarymentioning
confidence: 99%
“…Here, we build on several key reviews -4,18] to formalize and generalize ideas presented in recent theoretical (e.g., [23,32,39]) and empirical (e.g., [22,24,40]) papers. Our synthesis unifies…”
Section: Glossarymentioning
confidence: 99%
See 1 more Smart Citation
“…For animal groups, this form of model may be applied to decisions, for example, relating to movement in response to predators, or larger scale movements associated with migrations. In the latter case, there is substantial evidence to suggest that both the decision of whether to migrate or not [27] and the accuracy of migration [28,29] are affected by social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional research suggests that schooling has many aspects of benefits, such as improvements of navigational performance (Berdahl et al 2014;Torney et al 2015), hearing perception (Larsson 2009(Larsson , 2012, and foraging efficiency (Di-Poi et al 2014;Wang et al 2016). These benefits are modelled in a lumped manner as…”
Section: Objective Functionmentioning
confidence: 99%